The treasures : a novel - Evans, Harriet, 1974- (Sevenstones trilogy, 2025)
Every family's story starts somewhere. Alice and Tom's begins here. On the eve of her 16th birthday, Alice Jansen collects her treasures - the keepsakes, figurines and mementoes that help her make sense of her fragile family. But the next day her heart is broken, and the final treasure, a gift from her father, is lost. Two years later, Alice answers a phone call from a stranger and runs away to New York, and tries to forget her last golden summer at the orchard on the banks of the Hudson. Tom Raven can't understand why he keeps losing so many of the things and people that really matter to him, but he knows for certain that something important is missing from his life. One day, he remembers a forgotten letter and makes a phone call, then leaves Sevenstones, the only place that feels like home, for a strange city.